ASSISTANCE IN COORDINATING THE CONSOLIDATION OF ADDITIONAL OPD REPORTS - Joniarta, I Wayan; Pratama, I Putu Yuda; Indah Pratiwi, Nuning (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Consolidated Report is a report that brings together all financial reports made by all related OPDs in one government. In compiling consolidated reports, it is necessary to coordinate in preparing these reports, it is necessary to coordinate so that the reports prepared do not have discrepancies or discrepancies with those contained in the system. Continuous coordination and assistance will result in an efficient work cycle. The stages for preparing the consolidated report are regulated in Permendagri No 77 of 2020, Government Regulation Number 12 of 2019, Articles 189 to Article 193.